Development and validation of a high-throughput screening pipeline of compound libraries to target EMT - Jonckheere, Sven; Taminau, Joachim; Adams, Jamie; Haerinck, Jef; De Coninck, Jordy; Verstappe, Jeroen; De Clercq, Kato; Peeters, Evelien; Gheldof, Alexander; De Smedt, Eva; Goossens, Vera; Audenaert, Dominique; et al. (Cell Death and Differentiation, 2025)
Epithelial to Mesenchymal transitions (EMT) drive cell plasticity and are associated with cell features such as invasiveness, migration and stemness. They are orchestrated by select families of EMT-associated transcription factors, which exhibit pleiotropic roles in the malignant progression of various cancer types, such as breast and colorectal cancer (CRC). This has spurred interest in EMT as a promising target for the development of novel therapeutic strategies. In this study, we developed a phenotypic dual EMT Sensor screening assay, amendable to efficient high-throughput identification of small molecules interfering with EMT. In a proof-of-concept screening we identified anti-EMT repurposing drugs. From these, we validated RepSox, a selective inhibitor of the TGF-β type I receptor ALK5, and demonstrated that it is potently blocking EMT in both breast and colorectal cancer cell lines in vitro. In addition, utilizing a Drosophila melanogaster metastatic CRC model we confirmed the ability of the identified anti-EMT hits to suppress metastatic behavior in vivo.
CRIS-Team Scopus Importer:2025-05-16